Effect of Workload on Burnout among Healthcare Workers: Moderated by Perceived Organizational Support - Altaf, Zohra; Khattak, Aftab Khan (Pakistan Languages and Humanities Review, 2025)
The study aimed to investigate the relationship between workload and burnout, as well as perceived organizational support (POS), in healthcare workers in Islamabad, Pakistan. A total of 340 healthcare workers volunteered as participants in the study using a convenience sampling method. The variables of workload, burnout, and perceived organizational support were measured using self-report standardized measures (NASA Workload Inventory, Copenhagen Burnout Inventory, Survey of Perceived Organizational Support). The results from the Pearson correlations and multiple regression indicated that perceived workload significantly positively predicted burnout; perceived organizational support was significantly negatively correlated to burnout; and perceived organizational support significantly moderated the relationship between workload and burnout, with the value that the negative impact of workload was weaker in workers who perceived they had higher organizational support. The results of the study provide a dual-pronged aspect to combating burnout in that both work demands and an organizations climate can be addressed. Future recommendations incorporated that healthcare organizations should aim to support staff well-being through managerial support, NEAR equal voluntarily shared workload, acknowledgment of employee contribution, and curricular approaches that foster resilience